Locoregional mitomycin C injection for esophageal stricture after endoscopic submucosal dissection - Machida, H.; Tominaga, K.; Minamino, H.; Sugimori, S.; Okazaki, H.; Yamagami, H.; Tanigawa, T.; Watanabe, K.; Watanabe, T.; Fujiwara, Y.; Arakawa, T. (Endoscopy, 2012)
This prospective study aimed to evaluate the feasibility and safety of locoregional mitomycin C (MMC) injection to treat refractory esophageal strictures after endoscopic submucosal dissection (ESD) for superficial esophageal carcinoma. Patients with dysphagia and strictures that were refractory to repeated endoscopic balloon dilation (EBD) were eligible. After EBD, MMC was injected into the dilated site. Between June 2009 and August 2010, five patients were recruited. The treatment was performed once in two patients and twice in three patients with recurrent dysphagia or restenosis. In all patients, passing a standard endoscope through the site was easy and the dysphagia grade improved (grade 3→1 in 3 patients, grade 4→2 in 2 patients). No serious complications were noted. During the observation period of 4.8 months, neither recurrent dysphagia nor re-stricture appeared in any of the patients. The combination of locoregional MMC injections and EBD is feasible and safe for the treatment of esophageal strictures after ESD.Recently, endoscopic submucosal dissection (ESD) has been developed and accepted as a new endoscopic treatment for gastrointestinal tumors. ESD is a promising treatment for superficial esophageal carcinoma (SEC), and it has a reliable en bloc resection rate. However, the application of ESD for widespread lesions is challenging because of the high risk of the development of severe strictures, which lead to a low quality of life after ESD. Although endoscopic balloon dilation (EBD) is effective for benign strictures, it needs to be performed frequently until the dysphagia disappears 1. Mitomycin C (MMC), which is a chemotherapeutic agent derived from some Streptomyces species 2, reduces scar formation when topically applied to a surgical lesion. MMC has been applied to treat strictures in a variety of anatomical locations, including a variety of organs 3. The aim of this study was to prospectively evaluate both the feasibility and the safety of locoregional MMC injection therapy in patients with refractory esophageal strictures after ESD for SEC.